Finite element modeling of reinforced concrete beam using synthetic lghtweight coarse aggregate (SYLCAG) of offshore sand - Mohamad Hasrul, Jamaludin (2014)
Computer analysis can be used as an effectives tool to analyse structures and components without need to build the structures first. The analysis can be carried out in various condition and time with the verification of the actual condition under laboratory testing too. This study use a computer analysis program called ANSYS to verify what is actually occur to the structure such as beam during laboratory test. The research of lightweight concrete using SYLCAG that used for beam structure has been conducted and the result has been covered based on the theoretical and laboratory test. This study was conducted to analyse the flexural behaviour of the beams using ANSYS The manipulated variable of the beams are the concrete strength and beam density. The objectives that want to be achieved in this study are to understand the advantages of finite element method. Then, the result is compare between theoretical and experimental results. Besides that, the flexural behaviour of reinforced concrete and SYLCAG beam using ANSYS were studied. After the modeling and analysis were complete, the result proved that ANSYS manage to produce accurate result that similar to theoretical within 1% different for deflection for Beam A (Control) even though the experimental result was out of track. For other beams show the flexure behaviour within the manipulation of beam density and concrete strength. Somehow, ultimate moment capacity gives the closest result upon theoretical calculation for ACI 318 and Eurocode 2. This study concludes that the advantages of Finite Element Modeling (FEM) were discovering upon the accuracy of the result. Next is the comparison between theoretical and experimental gives relevant values and lastly the differences properties of the beams show the flexure behaviour.